Extended distribution of Kuepferia chateri (Gentianaceae) from India - Halder, A. K.; Jha, B. K.; Maity, D. (Rheedea, 2025)
Kuepferia chateri (T.N.Ho) Adr.Favre (≡Gentiana chateri T.N.Ho), an endemic species to Nepal, is recorded for the first time from Sikkim, India. A detailed taxonomic account, including description, photo-illustrations of diagnostic features, and habitat details are provided to validate this new addition to the flora of India.